2019
DOI: 10.1111/ppe.12573
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal risk factors associated with skin infection hospitalisation in Western Australian Aboriginal and Non‐Aboriginal children

Abstract: Background Hospitalisation with skin infection in Western Australian (WA) Aboriginal children is common, with the highest rates in infants and children from remote WA. Objective We aimed to quantify infant, maternal, and sociodemographic risk factors for skin infection hospitalisation in WA children, focussing on Aboriginal children aged <17 years. Methods We conducted a retrospective population‐based cohort study with linked perinatal and hospitalisation data on WA‐born children (1996‐2012), of whom 31 348 (6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…To our knowledge this association has not previously been described in Aboriginal children; however, both conditions occur more frequently in children where health inequities exist, including Indigenous, refugee and immigrant children [ 46 , 47 ]. In the pilot cohort, low birthweight was associated with a greater odds of ever having BSI, consistent with an earlier study of WA Aboriginal children that demonstrated low birthweight to be a risk factor for skin infection hospitalisation [ 48 ].…”
Section: Discussionsupporting
confidence: 87%
“…To our knowledge this association has not previously been described in Aboriginal children; however, both conditions occur more frequently in children where health inequities exist, including Indigenous, refugee and immigrant children [ 46 , 47 ]. In the pilot cohort, low birthweight was associated with a greater odds of ever having BSI, consistent with an earlier study of WA Aboriginal children that demonstrated low birthweight to be a risk factor for skin infection hospitalisation [ 48 ].…”
Section: Discussionsupporting
confidence: 87%
“…Smoke-free pregnancy can reduce the rate of hospitalization for skin infections in children by 9.6%. Smoking during pregnancy may lower the child's immunity and increase the risk of infection 155 .…”
Section: Smoking and Other Infections Skin Infectionsmentioning
confidence: 99%
“…The following were considered a priori to be potential risk factors for hospitalisation for infection 13,14 : sex, Aboriginal status, mode of delivery, gestational age, percent optimal birthweight, maternal smoking during pregnancy, maternal age, number of previous pregnancies, season of birth (based on temperate climate characteristics of metropolitan WA), socio-economic index for area, age group and length of stay (LOS) of index hospitalisation. Socioeconomic disadvantage was categorised by the Index of Relative Socioeconomic Advantage and Disadvantage, a summary statistic for a range of socio-economic indicators for the geographic area of residence, measured at the time of the child's birth and grouped into quintiles.…”
Section: Exposure Variablesmentioning
confidence: 99%